2017
DOI: 10.17507/jltr.0801.06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Information-processing-based Learning Cooperative Model on Speaking Skill Course

Abstract: Abstract-The speaking ability of university students is still low due to the lack of information, interaction, and critical ideas in oral communication. Cooperative learning was implemented as the approach to overcome it. The research aimed at: (1) evaluating the effectiveness of cooperative approach in terms of the development of student's speaking ability, the effectiveness of speaking learning activity, and the learning instruction of guidance book; 2) figuring out the significant difference result pre and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 6 publications
(2 reference statements)
1
32
0
4
Order By: Relevance
“…The development of creativity and liveliness of students is very crucial during the learning process. Creativity is very essential in life as it enables human to improve his life quality [10]. Students' creativity is needed in learning speaking.…”
Section: Introductionmentioning
confidence: 99%
“…The development of creativity and liveliness of students is very crucial during the learning process. Creativity is very essential in life as it enables human to improve his life quality [10]. Students' creativity is needed in learning speaking.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the cooperative approach, Darmuki (2017) suggested that first the students in one group should work together to fulfill the learning task. Second each group should contain students of blended abilities.…”
Section: Teaching Design Of Chaptermentioning
confidence: 99%
“…In order to solve this problem, software engineers, especially novice ones, need to be trained on the social topics starting from their student days since they feel themselves inadequate when making presentations [5]. In this way, the SE students can increase their public speaking abilities, which is one of the most important social skills sought in software engineers, before starting their careers [6].…”
Section: Introductionmentioning
confidence: 99%